2011
DOI: 10.1111/j.1558-5646.2011.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

PREDATOR‐INDUCED DEFENSE MAKESDAPHNIAMORE VULNERABLE TO PARASITES

Abstract: Predation is a major driver of natural selection. Phenotypic plasticity for the induction of defensive traits has proven to be a widespread mechanism for plants and animals to cope with the risk of consumption by herbivores and predators (Agrawal 2001). On theoretical grounds, inducible defenses are most likely to evolve when there is spatial or temporal heterogeneity in predation, and when there are reliable cues that can be used to indicate the future risk of attack (Lively 1986;Riessen 1992;Frank 1993;Hazel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 67 publications
4
62
2
Order By: Relevance
“…The fish density was similar to that used in previous studies [e.g. [23,24]]. The applied Triops density is lower to that found in natural concentrations of this predator (up to 2500 Triops/m² in natural ponds, [38]) and adequate for defence induction in D. magna [31].…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…The fish density was similar to that used in previous studies [e.g. [23,24]]. The applied Triops density is lower to that found in natural concentrations of this predator (up to 2500 Triops/m² in natural ponds, [38]) and adequate for defence induction in D. magna [31].…”
Section: Methodssupporting
confidence: 68%
“…Although Daphnia are often exposed to predators and parasites simultaneously, there are few studies that have investigated the effects of infection on inducible defences. It has been shown that Daphnia galeata can still express inducible defences against fish, regardless of infection with protozoan or yeast parasites [23,24]. The same was true for D. magna infected with a bacterial parasite [25].…”
Section: Introductionmentioning
confidence: 99%
“…Predators are also important: consumption of Daphnia by the dipteran larvae Chaoborus helps spread Metschnikowia by releasing fungal spores [43], while vertical migration by Daphnia to avoid fish predation brings putative hosts closer to spore-rich sediments [44]. And although direct costs of antipredator defences have been difficult to identify, recent evidence suggests an intriguing trade-off between the expression of morphological antipredator traits and vulnerability to parasitism [45].…”
Section: The Ecological Role Of Daphniamentioning
confidence: 99%
“…Another study also found costs of defences in Daphnia. Yin et al (2011) showed that defence against predators induced stronger disease progression in Daphnia. Here we show that the enhanced costs of defending against parasite spores, even if they do not cause visible infections, increase mortality upon Fig.…”
Section: Discussionmentioning
confidence: 99%